Levels of Renewable Energy Use in Selected European Union Countries – Statistical Assessment of Changes and Prospects for Development - Stec, Małgorzata; Grzebyk, Mariola; Caputa, Wiesława; Hejdukova, Pavlina (Comparative Economic Research. Central and Eastern Europe, 2024)
The search for and use of green energy sources is an important course of action for the European Union (EU). The paper compares the 13 EU countries that acceded to the EU in 2004 and afterwards in terms of the level of renewable energy use. The primary indicator used to assess the use of renewable energy sources (RES) was the share of renewable energy in gross final energy consumption from 2007 to 2021. Statistical data were sourced from the Eurostat database. The results of the study confirm that between 2007 and 2021, there were positive changes in the use of renewable energy in most of the countries. The prospects for renewable energy development in these countries were assessed by constructing forecasts of the indicator concerning the share of renewable energy in gross final energy consumption for 2022–2024. For most of the countries, the forecasts were highly and sufficiently precise, meaning the countries have a chance of meeting the RES targets set out in EU directives.